Literature study of Zn supplementation in feed for optimizing Nile tilapia Oreochromis niloticus growth - Muhammad Agus Suprayudi; Inarto, Hendri; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2024)
Micro minerals play a crucial role in the physiological processes of fish, acting as enzyme cofactors and stabilizing enzyme and protein structures. One of the essential micro minerals needed in the body is zinc (Zn). Zinc is utilized for various physiological processes, including the maintenance of enzymatic processes within the fish's body. The aim of this literature review is to analyze the optimal level of zinc supplementation in feed to enhance the growth performance of Nile tilapia (Oreochromis niloticus), based on the reported findings of conducted research. The literature sources were obtained from accredited national journals, international journals, research outcomes, theses, and dissertations over the past 20 years. The results of this literature review indicate that zinc supplementation in feed can have a positive impact on overall fish growth by increasing digestive enzyme activity, particularly protease enzymes. The level of zinc supplementation in fish is influenced by several factors including, fish size, feed consumption quantity, and duration of maintenance. The optimal dietary zinc intake for Nile tilapia growth is reported to be in the range of 20–50 mg/kg. Keywords: growth, literature study, Nile tilapia, zinc ABSTRAK Mikro mineral memiliki peran yang sangat penting dalam fisiologi tubuh ikan yang berfungsi sebagai kofaktor enzim dan menjadi penstabil struktur enzim maupun protein. Salah satu mikro mineral yang memiliki fungsi penting dan diperlukan dalam tubuh adalah unsur seng (Zn). Unsur Zn digunakan untuk proses fisiologis termasuk pemeliharaan proses enzimatik dalam tubuh ikan. Tujuan studi pustaka ini adalah menganalisis tingkat suplementasi Zn yang optimum dalam pakan untuk meningkatkan performa pertumbuhan ikan nila Oreochromis niloticus berdasarkan laporan hasil-hasil penelitian yang telah dilakukan. Sumber pustaka didapatkan dari jurnal nasional terakreditasi, jurnal internasional, hasil penelitian, tesis, dan disertasi pada kurun waktu 20 tahun terakhir. Hasil studi pustaka ini menunjukkan bahwa suplementasi Zn dalam pakan dapat memberikan pengaruh positif pada pertumbuhan ikan secara umum melalui peningkatan aktivitas enzim pencernaan terutama enzim protease. Tingkat suplementasi Zn pada ikan dipengaruhi oleh beberapa faktor diantaranya, ukuran ikan, jumlah konsumsi pakan, dan lama pemeliharaan. Nilai asupan Zn yang memberikan pertumbuhan optimum pada ikan nila adalah sebesar 20–50 mg/kg. Kata kunci: ikan nila, pertumbuhan, seng, studi pustaka